Report on Hand Printed Textile Industry at Madurai (Madras) - Planning Commission (Planning Commission, 1964)
Ordinary silk sarees with simple designs are patronized by the people in the South. Il has been reported that the Muslim Ladies of South have a Special fascination for these sarees whose price is only Rs. 10.50 each. A major part of the production is confined to such sarees only. However, enquiries made during the survey reveal that there has been a slow decline in production since 1961. Demand for the Madurai prints has registered a fall of 50% in 1963 as compared to 1961. This can be verified from the fact that the total sales for the year 1963 were only 60% of the production for the same year. Though the articles arc utilitarian, the changing fashion followed by growing competition from machine made prints have had their adverse influence on the demand. Keeping this in view, the following measures are recommended
Report on Hand Printed Textile Industry
Department of Social Security Government of India
Keywords: Summary of Conclusions and Recommendations; Economic Social background of area; Purpose of the Survey; Scope of the Survey; Methodology; Industry Trends and Key Statistics; Growth of Industry; Pattern of Ownership; Employment; Investment; Tools & Equipment's; Production Aspects; Cost Analysis; Raw Material; Marketing and Distribution; Relation between manufacturers & dealer; Cooperative Society; Value of production; Capital invested